Unilateral Palpebral Edema as a Central Sign of Acute Enterobacter-Associated Rhinosinusitis in a 5-Year-Old: A Rare Pediatric Case - Andrei Osman; Irina Enache; Alice Elena Ghenea; Alexandra Bucătaru; Sidonia Cătălina Vrabie; Ovidiu Mircea Zlatian (Reports)
Background and Clinical Significance: Acute pediatric rhinosinusitis is most commonly caused by Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. The involvement of Enterobacter species is rare and typically linked to chronic or nosocomial infections. Typical cases of acute rhinosinusitis in children present with abundant nasal discharge, headache, and fever and are generally managed with systemic antibiotics, nonsteroidal anti-inflammatory drugs (NSAIDs), mucolytics, and topical intranasal treatment. Atypical presentations prompt heightened clinical attention, and depending on the symptoms and patient status, surgical interventions might be considered. Case Presentation: We report the case of a previously healthy 5-year-old boy presenting with painful unilateral palpebral edema, minimal ipsilateral nasal discharge, and persistent headache despite standard rhinosinusitis therapy. Imaging tests revealed complete right maxillary sinus opacification. As the clinical response to ceftriaxone and dexamethasone was minimal, we opted for endoscopic sinus surgery. A nasal swab culture identified Enterobacter spp. in the nasal discharge. Conclusions: Unusual pathogens like Enterobacter spp. can cause acute sinusitis in children without prior risk factors. Early surgical intervention and culture-adjusted antimicrobial therapy remain critical for favorable outcomes.